Autobiografia em movimento: um estudo da comunicação dos afetos - Vieira, Ana Noronha (2021)
The goal of this dissertation is to reflect on the communication processes that emerge out of research experiences about autobiographies based on body movements, which do not necessarily lead to verbal narratives. From a cognitive perspective, verbal narratives are always embodied; however, these processes are not always explicit. The proposal of this dissertation is to discuss the relevance of movement in the process of communicating autobiographies, and how this process activates the construction of subjectivities – in other words, the communication per se of oneself and communication with others. The main hypothesis is that through so-called somatic education, BMC© and Ideokinesis, the body becomes aware of the movements that make up subjectivities and is ready to show these movements on a stage performance, thus creating a communication bond with the audience. The research is based on the corpomídia theory (KATZ and GREINER, 2005 and 2010), as well as on topics studied by researcher Ana Pais (2018), who has focused her work on empathy as a communication process in scenic arts. The empirical corpus is based on two projects, Ladies (2014) and LadiEX (2017), by theater and dance director Cristiane Paoli Quito. The expected results are to collaborate on a topic of relevance for the areas of communication and cultural policies – since the dissertation refers to the means of communication of the artistic experience with an audience, through empathy and a network of affection – and to advance the debates around political-philosophical matters that elaborate a notion of oneself in a less narcissistic way, opening up possibilities to reflect on the creation of collectives that go beyond neoliberal immunizing processes